Implementation of School Literacy Movement at Elementary School - Supriyanto Supriyanto; Yovitha Yuliejantiningsih; Titik Haryati (Universitas Negeri Semarang, 2025)
This study aims to: (1) Describe and understand the physical environment of the school literacy movement (GLS), (2) the role of the principal as an educator in the character development program To describe and understand the social environment of the school literacy movement (GLS) (3) Describe and understand the academic environment of the school literacy movement (GLS) at SD Negeri 1 Tanggel, Randublatung District, Blora Regency. The method used is qualitative research with a case study type. This study is located at SD Negeri 1 Tanggel Randublatung Blora. Data collection techniques use observation, interviews and documentation. Validation of data validity uses triangulation techniques with data sources. Data analysis techniques use data collection, data reduction, data display and conclusions. The results of the study show that: (1) the physical environment of the school literacy movement (GLS) includes a) the classroom environment has a reading corner used for independent reading. b) the office environment has media and posters. c) the school yard environment has a gazebo and reading garden, (2) the social environment of the school literacy movement (GLS) includes a) Appreciation. b) social support, c) budget support, (3) the academic environment of the school literacy movement (GLS) includes a) classroom learning b) reading movement 15 minutes before the lesson starts, c) Library visit movement during free time or on a certain schedule.Based on these findings, it is recommended that the principal improve the quality of the School Literacy Movement by adding several types of programs to support the literacy activities carried out and increasing the commitment of all school residents in carrying out school literacy activities, including teachers who teach to further develop various reading strategies carried out by all educators.